2023
DOI: 10.3390/biomedicines11030716
|View full text |Cite
|
Sign up to set email alerts
|

Computational and Preclinical Analysis of 2-(4-Methyl)benzylidene-4,7-dimethyl Indan-1-one (IPX-18): A Novel Arylidene Indanone Small Molecule with Anti-Inflammatory Activity via NF-κB and Nrf2 Signaling

Abstract: Background: The adverse effects of anti-inflammatory drugs urges the search for new anti-inflammatory agents. This study aims at the preclinical analysis of the in-house synthesized small molecule IPX-18. Human whole blood (HWB), peripheral blood mononuclear cells (PBMCs), and neutrophils were used. Rat basophil cells (RBL-2H3) were used to assess degranulation. Binding stability to NF-κB-p50 was predicted using computational docking and molecular dynamic simulations. Essential signaling proteins were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Paprocka et al investigated the anti-inflammatory activity of five natural SMs using LPS- LPS-stimulated PBMC, which showed that all derivatives significantly inhibited the production of pro-inflammatory cytokines, TNF and IFN-γ [ 261 ]. In another study, IPX-18 suppressed the production of IFN-γ, TNF, IL-8 and IL-2, with an IC 50 value of 96.29, 103.7, 122.9 and 105.2 nM by PBMC induced with 50 ng/mL of phorbol-12-myristate-13-acetate (PMA) [ 262 ]. In the IBD clinical setting, TNF increases effector T cells at the site of inflammation, while IFN-γ and IL-2 stimulate immune cells, and IL-8 recruits neutrophils and other immune cells to the site of inflammation [ 263 , 264 , 265 ].…”
Section: Screening Isolated Compounds For Anti-inflammatory Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Paprocka et al investigated the anti-inflammatory activity of five natural SMs using LPS- LPS-stimulated PBMC, which showed that all derivatives significantly inhibited the production of pro-inflammatory cytokines, TNF and IFN-γ [ 261 ]. In another study, IPX-18 suppressed the production of IFN-γ, TNF, IL-8 and IL-2, with an IC 50 value of 96.29, 103.7, 122.9 and 105.2 nM by PBMC induced with 50 ng/mL of phorbol-12-myristate-13-acetate (PMA) [ 262 ]. In the IBD clinical setting, TNF increases effector T cells at the site of inflammation, while IFN-γ and IL-2 stimulate immune cells, and IL-8 recruits neutrophils and other immune cells to the site of inflammation [ 263 , 264 , 265 ].…”
Section: Screening Isolated Compounds For Anti-inflammatory Propertiesmentioning
confidence: 99%
“…In the IBD clinical setting, TNF increases effector T cells at the site of inflammation, while IFN-γ and IL-2 stimulate immune cells, and IL-8 recruits neutrophils and other immune cells to the site of inflammation [ 263 , 264 , 265 ]. Hence, the ability of IPX-18 to reduce the production of pro-inflammatory cytokines signifies its anti-inflammatory potency [ 262 ]. Despite being widely used for anti-inflammatory screening, the PBMC assay has shown limitations or phenotypic differences between immune cells and those in the intestinal mucosa [ 237 , 257 ].…”
Section: Screening Isolated Compounds For Anti-inflammatory Propertiesmentioning
confidence: 99%